EFEKTIVITAS PENERAPAN MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM MENINGKATKAN MUTU PENDIDIKAN SD NEGERI 7 PEDUNGAN - Suryani, Ni Ketut; Ari Dwi Prasini, Ni Made; Chindytia; Surya Abadi, Ida Bagus Gede (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of School-Based Management (SBM) implementation in improving the quality of elementary school education at SD Negeri 7 Pedungan. The study employed a mixed methods approach with a descriptive research design. Data were collected through observations, interviews, documentation, and questionnaires involving the principal, teachers, and educational staff. The research instrument consisted of 73 indicators covering seven components of School-Based Management, namely curriculum management, student management, human resource management, financial management, facilities and infrastructure management, school-community relationship management, and excellent service management. Quantitative data were analyzed using percentage calculations, while qualitative data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of School-Based Management at SD Negeri 7 Pedungan achieved a total score of 206 out of a maximum score of 219, with a percentage of 94.1%, categorized as very good. The components of student management and excellent service obtained the highest percentage of 100%, indicating optimal educational management and professional service quality. However, several aspects still require improvement, particularly guidance and counseling services, supervision of learning improvement programs, and strengthening school-community partnerships. Therefore, effective implementation of School-Based Management contributes significantly to improving the quality of elementary education.